PERAN MANAJER RUMAH SAKIT DALAM PENGELOLAAN SUMBER DAYA MANUSIA SELAMA PENGENDALIAN WABAH PENYAKIT MENULAR BERBASIS PRINSIP EPIDEMIOLOGI (STUDI KASUS RSUD IBNU SINA) - Saputra, Ahmad Nurhadi; Rinawati (Asosiasi Ahli Administrasi Indonesia, 2026)
The outbreak of infectious diseases such as COVID-19 has put great pressure on the health care system, especially on the aspect of human resource (HR) management in hospitals. This study aims to analyze the relationship between the role of hospital managers and the effectiveness of HR management during a health crisis. The method used is quantitative correlational involving 172 respondents consisting of health workers and managerial staff in several referral hospitals. Data were collected through a closed questionnaire based on a Likert scale and analyzed using descriptive statistics and Pearson correlation tests. The results of the study indicate that there is a positive and significant relationship between the role of hospital managers, especially in the aspects of planning, directing, supervising, and crisis communication, with the effectiveness of HR management during an outbreak. This finding emphasizes the importance of strengthening managerial capacity and formulating adaptive HR policies to increase organizational resilience in dealing with health emergencies. This study is expected to be a reference in formulating hospital management policies and strategies in the future.